HIV does not replicate in naive CD4 T cells stimulated with CD3/CD28. - Roederer, M (1997)
In this report, we demonstrate that the T cell tropic strain of HIV, LAI, does not replicate in naive CD4 T cells stimulated by cross-linking CD3 and CD28. In contrast, LAI replicates well in memory CD4 T cells stimulated in the same way. Unlike this physiologically relevant stimulation, PHA stimulates productive LAI replication in both naive and memory T cells. These studies were conducted with highly purified (FACS-isolated) subsets of CD4 T cells identified by expression of both CD45RA and CD62L. Remixing of purified T cells showed that naive T cells do not suppress LAI replication in memory T cells and that memory T cells do not restore LAI expression in naive T cells. The suppression of productive LAI replication in naive T cells is not due to differential expression of viral coreceptors, nor is it due to inhibition of activation of the important HIV transcription factors, nuclear factor-kappaB and activator protein-1. The inherent resistance of naive T cells to productive HIV infection, coupled with their proliferative advantage as demonstrated here, provides a sound basis for proposed clinical therapies using ex vivo expansion and reinfusion of CD4 T cells from HIV-infected adults.